1995
DOI: 10.1007/bf02331834
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of a slowly inactivating high-voltage-activated calcium current by the neuropeptide FMRFa in molluscan neuroendocrine cells

Abstract: Using the whole-cell voltage-clamp technique, the effects of the neuropeptide Phe-Met-Arg-Phe-NH 2 (FMRFa) on two types of dihydropyridine-sensitive, high-voltage-activated calcium currents were investigated in isolated neuroendocrine caudo-dorsal cells (CDCs), which control egg-laying in the mollusc Lymnaea stagnalis. These currents are: (1) a transient current ('~inact = -10-25 ms) with an activation threshold of-40 mV and maximal amplitude at + 10 mV and (2) a sustained current ('Cinac t = -100-300 ms) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Selective modulability by neurotransmitters has been reported for L‐ and T‐type channels (Marchetti et al 1986), and for the L‐ and N‐type channels following the activation of a type B γ‐aminobutyric acid receptor in dorsal root ganglion neurones (Scott & Dolphin, 1986) or activation of a muscarinic receptor in rat sympathetic neurones (Wanke et al 1987). Recently, Dreijer et al (1995) reported selective modulability by FMRFamide of a high‐voltage‐activated calcium current in isolated neuroendocrine caudodorsal cells in the mollusc Lymnea stagnalis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective modulability by neurotransmitters has been reported for L‐ and T‐type channels (Marchetti et al 1986), and for the L‐ and N‐type channels following the activation of a type B γ‐aminobutyric acid receptor in dorsal root ganglion neurones (Scott & Dolphin, 1986) or activation of a muscarinic receptor in rat sympathetic neurones (Wanke et al 1987). Recently, Dreijer et al (1995) reported selective modulability by FMRFamide of a high‐voltage‐activated calcium current in isolated neuroendocrine caudodorsal cells in the mollusc Lymnea stagnalis .…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports of the action of FMRFamide on muscle ion channels but there is evidence for the direct action of FMRFamide on neuronal ion channels. Brezina et al (1989) demonstrated that FMRFamide‐induced inhibition of Ca 2+ currents in Aplysia abdominal ganglion neurones through a G protein pathway, and Dreijer et al (1995) found that FMRFamide evoked an inhibition of the slowly inactivating L‐type current in Lymnea caudodorsal neurones. Similarly, Man‐Son‐Hing & Haydon (1989) reported the inhibition of HVA currents in growth cones of isolated B5 neurones of Helisoma by FMRFamide, and this could be blocked by GDPβS and mimicked by intracellular dialysis of GTPγS.…”
Section: Discussionmentioning
confidence: 99%
“…In this context it is notable that in addition to TRP, crayfish amacrine neurons contain a FMRFamide-like peptide (Mangerich et al, 1988). In the mollusc Aplysia FMRFamide has potent presynaptic inhibitory effects (Belardetti et al, 1987;Sweatt et al, 1989;Dreijer et al, 1995;Klein, 1995) based on an enhancement of a K ϩ current and a reduction of a Ca 2ϩ current. On the contrary side, much evidence attests to excitatory effects of TRPs in both vertebrates (Maggio, 1988;Nakanishi, 1991) and arthropods (Blitz et al, 1995;Christie et al, 1997;Lundquist and Nässel, 1997), and there is also evidence that substance P antagonizes GABA action (Yamada and Akasu, 1996).…”
Section: Inhibitory Actions Of Gaba and Trpmentioning
confidence: 99%
“…It rapidly suppresses discharges of CDCs, both in situ and in isolated CDCs ( Brussaard et al, 1988 ). The inhibition by FMRFa in CDCs involves at least three different actions: inhibition of the voltage-activated sodium current ( Brussaard et al, 1990 , 1991 a ), suppression of the slowly inactivating HVA calcium current ( Dreijer et al, 1995 ), and activation of a potassium current ( Brussaard et al, 1988 ; and this paper). The simultaneous activation of three cooperative inhibitory mechanisms explains the strong inhibition of the CDCs by FMRFa.…”
Section: Discussionmentioning
confidence: 97%
“…This implies that the divergence of the FMRFa responses may occur at the level of the G-protein or the primary effector of the G-protein. A common signal transduction route is unlikely since the suppression of calcium channels is not mediated by the arachidonic acid pathway and probably involves a direct effect of the G-protein on the channel ( Dreijer et al, 1995 ), while stimulation of K + channels takes place via the arachidonic acid route. No data are available on the route by which sodium channels are affected.…”
Section: Discussionmentioning
confidence: 99%